Human Umbilical Cord Mesenchymal Stem Cells Attenuate Severe Burn-Induced Multiple Organ Injury via Potentiating IGF-1 and BCL-2/BAX Pathway. (23rd December 2022) - Wang, Hongyu; Ba, Te; Wang, Qiong; Yang, Longlong; Li, Chenyi; Hao, Xingxia; Yin, Yue; Liu, Lingying
Abstract : Background . Early multiple organ injuries induced by severe burn predict a high mortality. Mesenchymal stem cells (MSCs) are able to repair and reconstruct the injured tissues and organs induced by trauma and diseases. However, potential protective effect and mechanism of MSCs on multiorgan injury induced by severe burn at early stage remain to be not clarified. Therefore, this study was to explore the effect and mechanism of human umbilical cord-derived MSCs (hUCMSCs) against severe burn-induced early organ injuries in rats. Methods . Adult male Wistar rats were randomly divided into sham, burn, and burn+hUCMSCsgroups. GFP-labeled hUCMSCs or PBS was intravenous injected into respective groups. Migration and distribution patterns of GFP-labeled hUCMSCs were observed by inverted fluorescence microscope. The structures and cell apoptosis of the heart, kidney, and liver were measured by immunohistochemistry. Biochemical parameters in serum were assayed by standard Roche-Hitachi methodology. Western blotting was performed on these organs of rats in the three groups to explore the underlying mechanisms. Results . At 24 hours after hUCMSCs transplantation, we found that GFP-labeled hUCMSCs mainly localized in the blood vessel of the heart, kidney, and liver and a very few cells migrated into tissues of these organs. Compared with the sham group, structure damages and cell apoptosis of these organs were induced by severe burn, and systematic administrations of hUCMSCs significantly improved the damaged structures, cell apoptosis rates, and biochemical parameters of these organs. Furthermore, IGF-1 (insulin-like growth factor 1) level in burn+hUCMSCs group was significantly higher than that in the sham and burn groups. Meanwhile, severe burn induced BCL-2/BAX significantly decreased compared to the sham group, and it was markedly increased by hUCMSCs administration. Conclusion . The hUCMSCs transplantation can attenuate severe burn-induced early organ injuries and protect multiorgan functions by encouraging migration of hUCMSCs with blood circulation and increasing protective cytokine IGF-1 level and regulating BCL-2/BAX pathway of these vital organs. Furthermore, these data might provide the theoretical foundation for further clinical applications of hUCMSCs in burn areas.